Penerapan Konsep Pewarnaan Graf dalam Penyusunan Jadwal Perkuliahan Menggunakan Metode Algoritma Welch-Powell pada Program Studi Teknik Informatika Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tribuana Kalabahi - Landerius Maro; Lilis K. Sabu Purab (Peneliti.net, 2021)
In the academic world, the preparation of the lecture schedule on campus is related to the division of time, the availability of lecturers in each department and the availibility of lecture rooms. In the preparation of the lecture schedule, conflicts often occur between one schedule on another due to the limitations of the study space which is not balanced with the number of study groups, the room used for lectures is only four rooms while the study group has nine classes, namely in the first semester there are two classes, the third semster there are three classes, the fifth semester there are two classes, the seventh semester there are two classes. The informatics engineering department in the preparation of the lecture schedule is still manually so it takes a lot of time in its preparation. Schedule problems can be overcome with a technique that can optimize the preparation of the lecture schedule. One technique that can solve this problem is graph coloring, namely point coloring by utilizing the Welch-Powell algorithm so that an optimal solution is obtained with coloring results, namely the same color conducting lectures on the same day with different times and spaces